Metformin-Embedded Hydrogels: A Promising Approach for Accelerating Healing in Diabetic Ulcers - Zhou, Jiaru; Liu, Xiangmei; Tang, Tianyu; Liang, Jiawei; He, Huashen; Luo, Yingyao; Guo, Yanhua; Li, Peining; Ban, Junfeng; Zhang, Yan (Current Drug Delivery, 2025)
<span class=
Keywords: diabetic wound healing